汉越俚语的文化内涵对比研究 - Bùi Hồng Hạnh; truong ky tam; Nguyễn Thị Thanh Hương (Universitas Tanjungpura, 2022)
俚语作为民间非正式、较粗俗的口语形式，是一个民族语言和文化的瑰宝，是经过长期的历史沉淀形成的，具有深刻的文化内涵和鲜明的民族特色。汉越俚语文化对比研究对中越两国文化比较研究具有较大价值。本文通过对汉越俚语的思维方式、生活哲理、民族风俗、农业民俗方面进行对比，分析中越两国俚语异同的形成原因，为推动两国文化交流产生积极作用。Slang, as a folk informal and vulgar oral form, is the treasure of a national language and culture. It is formed through long-term historical precipitation and has profound cultural connotation and distinctive national characteristics. The comparative study of Chinese and Vietnamese slang culture is of great value to the comparative study of Chinese and Vietnamese culture. By comparing the thinking mode, life philosophy, national customs and agricultural folk customs of Chinese and Vietnamese slang, this paper analyzes the reasons for the similarities and differences between Chinese and Vietnamese slang, which plays a positive role in promoting the cultural exchanges between the two countries.